Preparation and Mechanical Properties of Polypropylene Composite for Seats - Mingzhe Yang (Chemical Engineering Transactions, 2018)
This paper describes the effects of the Multiwalled Carbon Nanotubes (MCNs)of different masses on the mechanical properties of polypropylene/calcium sulfate whisker composites for seats. With a twin roller open mill, a kind of composite PP-g-MAH/CSW/NWNTS may be made from surface-modified MCNs and modified calcium sulfate whiskers, polypropylene (PP), maleic anhydride grafted polypropylene (PP-g-MAH) using melt blending method, thereby to compare which effects the modified MCN of different doses plays on the mechanical properties of the PP/PP-g-MAH/CSW/NWNTS composites for sports seats. This study shows that the MCNs that have a mix-acid treatment on the surface uniformly disperse in the composite material, and well bond with the interface of the polymer matrix, thus playing a function for toughening and strengthening composite material. But worse, when the mass fraction of carbon nanotubes is higher, there is a phenomenon of agglomeration occurred, which in turn worsens the mechanical properties of the composite material. The carbon nanotubes at approx. 0.5%make the mechanical properties of the composite the best.